KUALTTAS BIOLOGI PERAIRAN SUNGAI SENAPELAN, SAGO DAN SAIL DI KOTA PEKANBARU BERDASARKAN BIOINDIKATOR PLANKTON DAN BENTOS - Suwondo '; Elya Febrita; Dessy '; Mahmud Alpusari (Biogenesis, 2004)
Water quality based on plankton and benthic organism as bio-indicators  in Senapelan,  Sago and Sail Rivers at  Pekanbaru  city  were  investigated  on  April  -   August  2003.  Survey  method  with  purposive  random sampling  at 7  sampling  point  was  used  in the research.  Various  parameters  such  as saprobe  coefficient indexes,  plankton  and benthic  diversity  and also  bio-indexes  benthic  organism  were observed   Final results had  shown that saprobe indexes plankton between -  0,85   until   +  1,00. While diversity indexes benthic organism  between  0,1 16  -   1,335  and  bio-indexes  benthic  between  1  until  5.  Based  on  the  criterion expressed  that water quality of biology  in Senapelan,  Sago and Sail Rivers at Pekanbaru city were middle until heavily polluted.   Key  words : Biology Quality, Plank tonic, Benthic